Pengendalian Keselamatan dan Kesehatan Kerja di Departemen HSSE Pt.Pertamina EP Asset 4 Sukowati Field - Ekoprastiyo, Ekoprastiyo; Ashari, Faisal (Universitas Bojonegoro, 2022)
Potential hazards that can cause work accidents can come from various work activities carried out in work operations and can also come from outside the scope of work. Therefore, the implementation of an occupational safety and health program is in the form of implementing an OHS management system, including through identification of hazards and recommendations for effective control measures, so as to create a safe, healthy and prosperous work environment. PT. Pertamina asset 4 Sukowati Field is an energy company, which is engaged in the oil and gas industry, including exploration and production, which is located in Bojonegoro, East Java province. In the oil and gas production process, there are many potential hazards in various work activities. Within a company, there are potential hazards in the operation and repair of equipment. Some of these hazards are high pressure, high temperature, falling objects, automatic systems that can cause pinching, mechanical, high electrical voltage, noise from loud engine sounds, chemicals, exposure to toxic H2S gas. The purpose of this research is to know the occupational health and safety control system, to know the process of B3 waste treatment, and to know how to maintain fire fighting equipment. The data collection method used is participation where the author is directly involved in internship activities regarding occupational health and safety control programs, field observations where researchers monitor or direct observations in the field, in order to know firsthand about safety at work, and interviews by asking direct questions. to the staff of the department on the science of occupational safety and health in the workplace. the results of the research conducted, it was found that in order to maintain the safety and health of its employees, the company provides work safety facilities, all workers must care and be aware of work safety, in order to maintain health in the form of free treatment, sports facilities and adequate food and nutrition allowances. So the risk of work accidents will be smaller. Actions to manage waste or B3 materials used in the production operation process will be handled in accordance with the Material Safety Data Sheet (MSDS). The processing of B3 waste begins with temporary storage in a special storage room that has a permit from the KLHK/DLH/Governor/Regent to be sent to a B3 waste collection/processing company that has a permit from the KLHK, or also known as a third party. Periodic maintenance is required according to standard maintenance procedures.